Rediscovering Crops: DNA species identification and ethnobotanical investigation of chenopods in the eastern Himalayas - You, Ting; Wang, Linying; Gao, Yu; Tian, Yaofei; Yang, Qi; Yang, Xiaoyan (Ethnobiology and Conservation, 2025)
One strategy responding to global food security challenges is to enhance the utilization of ancient and under-exploited niche crops. As Quinoa garnered considerable attention recently, research on chenopods in Asia has not kept pace. This study launched a field investigation on the cultivation and use of chenopods in the southern foothills of the eastern Himalayas, an area that may serve as a center for chenopods domestication. By employing DNA analysis, we identified the species involved. As highly adaptable crops, Chenopods are typically cultivated using intercropping practices to support sustainable agricultural production in this region. Our findings reveal for the first time that the chenopods cultivated in this region originated from Chenopodium album, but over time, due to prolonged human selection and environmental influences, distinct morphological traits and genetic variations have emerged, leading to localized varieties. Based on phylogenetic, morphological and spatial distribution analysis, we propose the existence of multiple independent domestication centers of chenopods in Asia. This study not only sheds light on the origin and domestication of chenopods in Asia but also underscores the strategic potential of their nutritional value and unique cultivation practices in addressing climate change, enhancing global food security, and contributing to the achievement of the Sustainable Development Goals.